INDIGENOUS TRADITIONAL TECHNICAL KNOWLEDGE OF DISEASE CURE AND PREVENTION THROUGH FISH CONSUMPTION - Pandey, B. N.; Sing, Ranjit; Kumar, Dilip; Pandey, P. N. (Journal of Indian Fisheries Association, 2010)
Our knowledge regarding ethno â€“ medico zoology is scanty and scattered. The present work is an endeavour to collect information on indigenous traditional knowledge (ITK) of disease cure through fish consumption, prepare a consolidated report on this aspect and to document our ITK so that in the long run after due verification (by Medical experts), such ITK can be patented. We also suggest for the recognition of the age old tribal medicine and establishment of a national research institute for tribal medicines at suitable place for the welfare of all the human beings. Â Key words: Disease cure, Fish consumption, Indigenous traditional knowledge.